2019
DOI: 10.31487/j.scr.2019.06.11
|View full text |Cite
|
Sign up to set email alerts
|

Listeria Monocytogenes Prosthetic Joint Infection, Case Report and Review of the Literature

Abstract: Background: Listeria monocytogenes causes bacteraemia in elderly and immunocompromised patients and rarely also in immunocompetent patients. In sporadic setting it can be challenging to diagnose. We present the first case of Listeria monocytogenes infection presenting as an acute infection of a prosthetic joint in an immunocompetent patient. Case summary: An immunocompetent patient presented with acute onset of right hip pain lasting for 3 days. The day before admission the patient had fever of 38.5°C and chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In a recent study of 294 hips and knees, infection caused by LM was reported at a rate of 0.7%. We have found 67 cases with PJI caused by LM in English Literature (from 1987 until 2020) [ 2 , 3 , 5 , 20 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ] ( Table 1 ). The mid-time from initial surgery to the onset of infection caused by LM in the prior literature was 6.8 years (range, 2 mo-21 y) whereas in this case was 9 years postoperatively ( Table 1 , Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent study of 294 hips and knees, infection caused by LM was reported at a rate of 0.7%. We have found 67 cases with PJI caused by LM in English Literature (from 1987 until 2020) [ 2 , 3 , 5 , 20 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ] ( Table 1 ). The mid-time from initial surgery to the onset of infection caused by LM in the prior literature was 6.8 years (range, 2 mo-21 y) whereas in this case was 9 years postoperatively ( Table 1 , Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kleemann et al reported a recurrent infection 2 years after initial conservative treatment [ 9 ]. Of 9 patients (13.2%) treated with debridement 7 were reported to have good results over a 3-month to 20-month follow-up period, but 2 patients had implants removed later [ 5 , 6 , 14 , 20 , 24 , 32 , 33 , 36 ]. All were acute cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations